The Convergence of AI and Television: Transforming Ad Monetization in the Digital Era - Godleti, Srihari Babu (International Journal of Computing and Engineering, 2025)
This article examines the revolutionary impact of artificial intelligence on television advertising monetization. It explores how AI technologies are creating new pathways for converting viewer engagement into direct purchases, thereby reshaping traditional advertising revenue models. The convergence of AI and television has fundamentally transformed the traditional awareness-based advertising paradigm into an interactive commerce ecosystem where entertainment, advertising, and e-commerce boundaries blur. By investigating the technical foundations, implementation models, economic impacts, and consumer behavior factors that drive this transformation, the article provides a comprehensive framework for understanding how AI-driven shoppable TV is creating value for stakeholders across the television ecosystem while simultaneously reshaping viewer experiences and expectations.